Do Informal Referrals Lead to Better Matches? Evidence from a Firm's Employee Referral System - Meta Brown; Elizabeth Setren; Giorgio Topa (Institute for the Study of Labor (IZA), 2014)
Using a new firm-level dataset that includes explicit information on referrals by current employees, we investigate the hiring process and the relationships among referrals, match quality, wage trajectories and turnover for a single U.S. corporation, and test various predictions of theoretical models of labor market referrals. We find that referred candidates are more likely to be hired; experience an initial wage advantage which dissipates over time; and have longer tenure in the firm. Further, the variances of the referred and non-referred wage distributions converge over time. The observed referral effects appear to be stronger at lower skill levels. The data also permit analysis of the role of referrer-referee pair characteristics.
Keywords: J30; J63; J64; 330; referrals; human resources; turnover; wage trajectory